Reinforcement and Punishment: The Concepts Teachers Need to be Carefully Watched - Haiyudi, Haiyudi; Reranta, Redika Cindra; In, Sitthipon Art- (IJECA (International Journal of Education and Curriculum Application), 2023)
Abstract: Numerous acts done by teachers without proper consideration were impactful to students. This study determines the level of teacher cognition to reinforcement and punishment concept in the learning process at school. In addition, this study also aims to assign the accuracy of applying these concepts to students. Mixed-method using embedded design was implemented to address the goals. As 49 teachers responded from several schools in the District of Kepulauan Pongok, South Bangka. Besides, in-depth interviews were also conducted with five teachers who were selected. The research sample was set based on purposive sampling. The data collection techniques were a questionnaire in the form of a rating scale and an in-depth interview form with a feasibility test previously performed using the Content Validity Index. Likewise, the data obtained were processed using the calculation of the average, standard deviation, percentage as well as content analysis. The results indicated that 2.86 out of 5 or 57.2% of the teachers had good understanding towards the two concepts. Meanwhile, 3.15 or 63% of the teachers were familiar to reinforcement. Besides, 2.44 or 4.88% of the teachers were familiar to give punishment.  In other words, the comprehension as well as it application are classified very moderate and needed to be carefully watched.